Microfluidic production of perfluorocarbon-alginate core-shell microparticles for ultrasound therapeutic applications - Duarte, Ana Rita C. (2014)
The fabrication of micrometer-sized core−shell particles for ultrasound-triggered delivery offers a variety of applications in medical research. In this work, we report the design and development of a glass capillary microfluidic system containing three concentric glass capillary tubes for the development of core−shell particles. The setup enables the preparation of perfluorocarbon-alginate core−shell microspheres in a single process, avoiding the requirement for further extensive purification steps. Core−shell microspheres in the range of 110−130 μm are prepared and are demonstrated to be stable up to 21 days upon immersion in calcium chloride solution or water. The mechanical stability of the particles is tested by injecting them through a 23 gauge needle into a polyacrylamide gel to mimic the tissue matrix. The integrity of the particles is maintained after the injection process and is disrupted after ultrasound exposure for 15 min. The results suggest that the perfluorcarbon-alginate microparticles could be a promising system for the delivery of compounds, such as proteins, peptides, and small-molecule drugs in ultrasound-based therapies.